Survey on Permissive Parenting Patterns in Students of the Guidance and Counseling Study Program - Faisal Basri; Siti Rahmi (ASHA Publishing, 2026)
This study aims to describe the permissive parenting style experienced by students of the Guidance and Counseling Study Program at the University of Borneo Tarakan. The research employed a quantitative approach with a descriptive survey design. The population consisted of students in the Guidance and Counseling Study Program, with a sample of 50 students selected through simple random sampling. Data were collected using a closed-ended questionnaire based on five indicators of permissive parenting: unlimited freedom, lack of supervision, lack of firmness in rules, always complying with children's wishes, and lack of discipline. The instrument was tested for validity and reliability before data collection. Data were analyzed using descriptive statistics, including frequencies, percentages, mean scores, and score interval categorization. The findings revealed that permissive parenting was generally categorized as very high. The most dominant indicator was always complying with children's wishes, followed by unlimited freedom, lack of supervision, lack of firmness in rules, and lack of discipline, indicating high freedom and relatively low parental control.